Mengungkap Permasalahan Pembiayaan Sistem Bagi Hasil dan Islamisasi Teori Keagenan - Ahmad Roziq (IAI Darussalam, 2020)
This study aims to reveal the problem of the profit-sharing system and the solution to the problem. This research uses a qualitative approach and a kasyif analysis. A qualitative approach is used to reveal empirically to find solutions to the problem of profit-sharing system financing. Meanwhile, the kasyif approach is used to analyze the problems and financing solutions for the profit-sharing system based on the perspective of Islamic law. This study uses a case of implementation of profit-sharing systems in Islamic banking. The results of the study concluded that it is necessary to internalize the values ​​of sharia (Islamic sharia ethics) in agency theory or it is necessary to reconstruct agency theory into